The promotion of UNESCO biosphere reserves as tourist destinations: a preliminary examination of trends and implications. (1st January 2013) - Ryan, Jason; Silvanto, Sari; Seitz, Victoria
This article explores the extent to which UNESCOs man and the biosphere (MAB) programme is being used by national tourist organisations (NTOs) to promote tourism and examines the impact of tourism on the central purpose of the MAB programme: developing sites of excellence where new and optimal practices to manage nature and human activities are tested and demonstrated. The article specifically examines how extensively the UNESCO biosphere designation is being used by NTO websites to encourage tourism and whether the biosphere reserves that are being promoted as tourist destinations and attractions are in countries that score favourably on the environmental performance index (EPI), a rating of countries on performance indicators covering environmental public health and ecosystem vitality. The study finds that, on average, countries that promote biosphere reserves as tourist destinations tend to have better environmental records than countries that do not. Further research, especially case studies, is needed to confirm these findings. This study also identifies major trends and issues concerning the use and management of UNESCO biosphere zones as tourist attractions.